What are the pharmacotherapy options for treating prediabetes?. (October 2014) - Daniele, Giuseppe; Abdul-Ghani, Muhammad; DeFronzo, Ralph A
<x xml:space="preserve">Abstract</x> Introduction: The incidence of type 2 diabetes mellitus (T2DM) has risen to epidemic proportions, and this is associated with enormous cost. T2DM is preceded by 'prediabetes', and the diagnosis of impaired glucose tolerance (IGT) and/or impaired fasting glucose (IFG) provides an opportunity for targeted intervention. Prediabetic subjects manifest both core defects characteristic of T2DM, that is, insulin resistance and β-cell dysfunction. Interventions which improve insulin sensitivity and/or preserve β-cell function are logical strategies to delay the conversion of IGT/IFG to T2DM or revert glucose tolerance to normal. Areas covered: The authors examine pharmacologic agents that have proven to decrease the conversion of IGT to T2DM and represent potential treatment options in prediabetes. Expert opinion: Weight loss improves whole body insulin sensitivity, preserves β-cell function and decreases progression of prediabetes to T2DM. In real life long-term weight loss is the exception and, even if successful, 40 – 50% of IGT individuals still progress to T2DM. Pharmacotherapy provides an alternative strategy to improve insulin sensitivity and preserve β-cell function. Thiazolidinediones (TZDs) are highly effective in T2DM prevention. Long-acting glucagon-like peptide-1 (GLP-1) analogs, because they augment β-cell function and promote weight loss, are effective in preventing IGT progression to T2DM. Metformin is considerably less effective than TZDs or GLP-1 analogs.